2014
DOI: 10.1371/journal.pone.0113453
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Perfluorooctane Sulfonate Induces Behavior Defects and Neurotoxicity through Oxidative Damages, In Vivo and In Vitro

Abstract: Perfluorooctane sulfonate (PFOS) is an emerging persistent pollutant which shows multiple adverse health effects. However, the neurotoxicity of PFOS and its mechanisms have not been fully elucidated. Using a combination of in vivo and in vitro methods, the present study provides a detailed description of PFOS-induced neurotoxicity. Results showed that the median lethal concentration of PFOS was 2.03 mM in Caenorhabditis elegans for 48 h exposure. 20 µM PFOS caused decrease of locomotor behaviors including forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…Multiple toxic effects of PFOS have been demonstrated in previous studies (Lau et al 2007;Ahrens and Bundschuh 2014;Chen et al 2014). For the first time, our results revealed that chronic exposure to PFOS affected longevity of animals.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Multiple toxic effects of PFOS have been demonstrated in previous studies (Lau et al 2007;Ahrens and Bundschuh 2014;Chen et al 2014). For the first time, our results revealed that chronic exposure to PFOS affected longevity of animals.…”
Section: Resultssupporting
confidence: 73%
“…Age-synchronized nematodes were produced for experiments by collecting adult nematodes into tubes by washing plates with M9 buffer, and then dissolving the adults using a bleach-containing buffer (0.45 N NaOH, 2 % HClO) to release eggs. The eggs were collected and hatched on the plates without food, then synchronized for experiments (Chen et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johansson et al (2008Johansson et al ( , 2009) speculated that PFOS exposure could affect processes linked to neurodegeneration, thereby af fecting cognitive function. Chen et al (2014) re ported that in Caenorhabditis elegans, PFOS induced ob vious behavioral defects (e.g. the decline of chemo taxis learning ability) and neurotoxicity via oxidative stress damages.…”
Section: Discussionmentioning
confidence: 96%
“…Most toxicological tests concerning PFOS in fish have focused on metabolic, reproductive and developmental aspects (Hagenaars et al 2008, Han & Fang 2010, Dorts et al 2011. However, there is limited but growing evidence linking PFOS exposure to the toxic contamination of the central nervous system (Austin et al 2003, Johansson et al 2009, Chen et al 2014. As reported by Johansson et al (2009), PFOS exposure can affect processes linked to neurodegeneration, thereby affecting cognitive function.…”
Section: Introductionmentioning
confidence: 99%